Young people, school experience and violence in the context of urban poverty (Palimpsesto, 2018)
This work aims to describe the experiences of youth violence in contexts of urban poverty, recoveringresults from an audiovisual production experience carried out in a secondary school of the San Martíndistrict (Buenos Aires, Argentina). The hypothesis is that although students experience violent situationsin their neighbourhoods as much as they suffer the deep conditions of poverty, inequality andenvironmental degradation in a daily basis, it is within the school space that they problematize their ownexperiences making them visible. We analyze this hypothesis using the results of three documentaries2 inwhich students describe in different ways the meanings of violence, its causes, how it affects them andtheir possibilities of thinking about the ways to improve their life situations.
Keywords: young boys; scholarship; experiences; violence; poverty